2011
DOI: 10.1094/phyto-01-11-0023
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol Biosynthesis-Related Gene Expression During Wheat Kernel Colonization by Fusarium graminearum

Abstract: Deoxynivalenol (DON) is a potent mycotoxin and virulence factor produced by Fusarium graminearum. We examined the expression of the core DON biosynthetic gene Tri5 during wheat head infection of susceptible and resistant cultivars and susceptible cultivars treated with strobilurin fungicides (e.g., azoxystrobin). DON was quantified to correlate expression with toxin accumulation. The highest Tri5 expression relative to housekeeping genes occurred at the infection front. As infection progressed, earliest-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 47 publications
5
50
1
Order By: Relevance
“…Deoxynivalenol (DON) produced by Fusarium graminearum is a potent B-type trichothecene mycotoxin [33] and virulence factor to disease formation in wheat floral tissue [34]. Commonly found in harvested cereal grains, DON lowers grain quality and is a serious health concern to humans and animals [35].…”
Section: The Gene Annotationmentioning
confidence: 99%
“…Deoxynivalenol (DON) produced by Fusarium graminearum is a potent B-type trichothecene mycotoxin [33] and virulence factor to disease formation in wheat floral tissue [34]. Commonly found in harvested cereal grains, DON lowers grain quality and is a serious health concern to humans and animals [35].…”
Section: The Gene Annotationmentioning
confidence: 99%
“…DON functions as a virulence factor in the colonization of wheat by F. graminearum, allowing hyphae to colonize the rachis node and move from spikelet to spikelet (Brown et al, 2010;Jansen et al, 2005). DON has been shown to be most active at the infection front and transcription of DON biosynthesis genes has been detected within 24 h of initial infection (Hallen-Adams et al, 2011). DON levels have also been shown to increase in wheat tissue up to 45 DAA and to be positively influenced by increased levels of moisture during grain fill up to 30 DAA (Cowger and Arellano, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…DON is produced early in the interaction, in specialized infection structures [103] and TRI genes are transcribed in the moving infection front [104]. An immunohistochemistry study with antisera raised against DON showed that DON can move ahead of the fungus and presumably conditions susceptibility by interfering with translation.…”
Section: Trichothecenesmentioning
confidence: 99%